Kidney stone and urinary bladder telangiectasia in a patient with TAR syndrome - Akil, İpek; Gözmen, Salih; Yılmaz, Ömer; Taneli, Can (The Turkish Journal of Pediatrics, 2008)
TAR syndrome is a congenital malformation syndrome characterized by bilateral absence of the radius and thrombocytopenia. The known urinary anomalies are duplex ureter, dilatation of renal pelvis, horseshoe kidney and functional problems like vesicoureteral reflux and pyelonephritis. In this report of a case with TAR syndrome, a kidney stone and bladder telangiectasia were found coincidentally during the investigation of hematuria. TAR syndrome is discussed in the light of the medical literature. To our knowledge, no case has been reported demonstrating nephrolithiasis and bladder telangiectasia in TAR patients.